Supernatural Beliefs in Saap Khunsai Novel Series - หยังกุล จันทร์จิรา; Sangmanee, Nantaporn (RUSAMILAE JOURNAL, 2022)
to analyze supernatural beliefs in 4 horror novels in Saap Khunsai series, namely, Prai Kuman by RabbitRose, Osot Rod Leud by Ployfon, Pang Asura by Naii Mok, and Reun Rak Tamnak Khaen by Suriyathit. The analysis results show 5 types of supernatural beliefs appearing in the series: 1) Belief in law of karma-the cause and effect of the character’s actions, appearing in the story only as a result of their evil deeds, 2) Superstitious belief-the state after death that appears to human beings as ghost with two characteristics, a good one that appears in an intact shape and a demon one that appears hideous, 3) Belief in black magic-a subject of superstition used to harm others, appearing in 3 types, "ya sang" (death potion), "sek khong khao tong" (conjuring harmful object into one’s stomach using black magic), and "namman prai" (devil juice), 4) Belief in amulet power-a sacred item believed to be used for protection of its posessor, appearing in 3 types, "bia kae" (amulet made of a type of clam’s shell), "soi long akhom" (cursed necklace) and "Takrud" (tiny rolled metal amulet inscribed with sacred words), and supernatural beliefs, and, 5) Belief in mystical forest-a mysterious power and supernatural phenomena occurring in the forest.